Desarrollo de un plan institucional de reducción de riesgos para la Unidad Educativa Técnica Particular Centebad de la ciudad de Lago Agrio. - Quinllin Tituana, Rony Wladimir (2024)
The main objective of this research study, entitled " Desarrollo de un Plan Institucional de Reducción de Riesgos para la Unidad Educativa Técnica Particular Centebad de la Ciudad de Lago Agrio” establishes an analysis of risk management based on the hazards that members of the educational community are exposed to in the Lago Agrio canton. The initial risk level of the Unidad Educativa Técnica Particular Centebad is 18 points, establishing the criterion of Medium (III) with a tendency towards high risk, which enables the development of activities to be carried out to mitigate the effects of the risks present due to the hazards within the Institution. The identification of the risks present in the Unidad Educativa Técnica Particular Centebad in the city of Lago Agrio through the guidelines established by the Education District 21D02 establishes initial parameters of analysis such as the identification of the level of risk, the main vulnerabilities of the institution, the formation of brigades for emergency management until establishing the necessary resources to prevent consequences in the development of an adverse event and strengthening the response capacities of teachers, administrative staff to protect the integrity of the educational community (students). The development of the maps and other components presented in the PIRR format within the educational institutions reflects the need to create a culture of prevention that starts with the pupils, and prioritizes the integral security of all the members of the educational community of the educational unit.